2019
DOI: 10.1186/s10194-019-1027-7
|View full text |Cite
|
Sign up to set email alerts
|

A real-world study on unmet medical needs in triptan-treated migraine: prevalence, preventive therapies and triptan use modification from a large Italian population along two years

Abstract: BackgroundAlthough migraine is a disabling neurological condition that causes important disability, it remains an area of underdiagnosis and undertreatment worldwide. The aim of this study was to depict the burden of the unmet medical needs in migraine treated with triptans in a large Italian population.MethodsA 2-year longitudinal analysis of migraineurs with unmet medical needs on treatment with triptans was performed. The studied cohort consisted of subjects with ≥4 triptan dose units per month, selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 36 publications
6
27
0
1
Order By: Relevance
“…Effects of preventive treatments on migraine frequency. There was only a mild effect on headache frequency in the three months following preventive drugs prescription, in accord to previous studies based on indirect evidence (3,16,20). This could suggest that there is a bias between Randomized…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Effects of preventive treatments on migraine frequency. There was only a mild effect on headache frequency in the three months following preventive drugs prescription, in accord to previous studies based on indirect evidence (3,16,20). This could suggest that there is a bias between Randomized…”
Section: Discussionsupporting
confidence: 87%
“…General considerations on headache populations These real life data showed that in our south Italy tertiary headache center, the most of patients suffered from medium-high frequency migraine, not previously treated with preventive drugs, and only a minority of them used triptans. An Italian study [3] showed that only a minority of patients using triptans and worthy of prophylaxis, assumed preventive drugs, that means that they did not have access to headache specialist or center, or that they had scarce compliance to the prescribed treatment, or they withdraw for adverse events. Our impression is that the most of patients were addressed to our center for a medium-high frequency migraine that was previously underestimated, though worthy of preventive treatment and triptans prescription.…”
Section: Discussionmentioning
confidence: 99%
“…These real-life data show that in our tertiary headache center in South Italy, most of the patients suffered medium-high frequency migraine, they were not previously treated with preventive drugs, and only a minority of them used triptans. An Italian study [3] showed that only a minority of patients using triptans and that qualified for prophylaxis used preventive drugs. Therefore, they did not have access to headache specialists or centers, minimally complied with the prescribed treatment, or withdrew because of adverse events.…”
Section: General Considerations Regarding Headache Populationsmentioning
confidence: 99%
“…In the same population, amitriptyline was the most prescribed drug, followed by topiramate (6.3%), propranolol (3.3%) and atenolol (2.7%). The rate of improvement was estimated on the basis of the reduction in triptan use; the use of triptans was even significantly lower among subjects treated with oral preventive therapies than among those without these drugs, though mild improvement was present in the group with chronic migraine [3]. The study underlined that the current use of preventive therapies is limited and has negligible benefits and that most migraine patients currently have unmet needs.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation